Formal and Informal Language Expressions Used by English Students of Indonesia in Classroom Presentation-Interaction - Muslimawati, Nurfitri Sri (Elsya : Journal of English Language Studies, 2022)
Analysing communication strategies remains crucial to overcome communication problems in classroom interaction since it directs the students to receive successful English learning results. One strategy to communicate is applying an appropriate language level of formality in the classroom. However, there have been very limited researches that explore formal and informal languages in the classroom context. This research aims to discuss the characteristics and factors influencing students in using formal and informal expressions in the classroom presentation-interaction. This research applied a qualitative method taking twenty-two students of Universitas Negeri Makassar as participants. The data from classroom observation, voice-recording, and interview were analysed using the discourse analysis approach. The result of the research shows that characteristics of formal and informal language are absolutely opposite, namely complete versus uncompleted sentence, politeness versus familiarity words, and precise versus colloquialism words. The result of the research also shows factors influencing the use of formal and informal language are formal situations, communication purposes, status and age differences, and familiarity. This research also found the relation of using formal language as students' strategies to be polite to the lecturer in classroom interaction. Results of this research are significant for students in shaping good strategies in using formal or informal language expressions to achieve effective communication in classroom interaction.